A Framework of Best Practice of Continuing Professional Development for the Accounting Profession - De Lange, Paul; Jackling, B.; Basioudis, I. (Routledge, 2013)
The International Accounting Education Standards Board (IAESB) places a strong emphasis on individual professionals taking responsibility for their Continuing Professional Development (CPD). On the other hand, the roles performed by professional accountants have evolved out of practical necessity to ‘best’ suit the diverse needs of business in a global economy. This diversity has meant that professional accountants are seen in highly specialised roles requiring diverse skill sets. In order to enhance the contribution of the accountant as a knowledge professional for business, it follows that CPD that leverages off an individual’s experience should be designed to meet the needs of professionals across the different specialised roles within the profession. In doing so the project identifies how CPD should differ across roles and levels of organisational responsibility for accounting professionals. The study also makes a number of policy recommendations to IAESB and IFAC.